Systematic estimation of biological age of in vitro cell culture systems by an age-associated marker panel - Hartmann, Christiane; Herling, Luise; Hartmann, Alexander; Köckritz, Verena; Fuellen, Georg; Walter, Michael; Hermann, Andreas (Frontiers in Aging, 2023)
Aging is a process that affects almost all multicellular organisms and since our population ages with increasing prevalence of age-related diseases, it is important to study basic processes involved in aging. Many studies have been published so far using different and often single age markers to estimate the biological age of organisms or different cell culture systems. However, comparability of studies is often hampered by the lack of a uniform panel of aging markers. Consequently, we here suggest an easy-to-use biomarker-based panel of classical aging markers to estimate the biological age of cell culture aging systems that can be used in standard cell culture laboratories. This panel is shown to be sensitive in a variety of aging conditions. We used primary human skin fibroblasts of different donor ages and additionally induced either replicative senescence or artificial aging by progerin overexpression. Using this panel, highest biological age was found for artificial aging by progerin overexpression. Our data display that aging varies depending on cell line and aging model and even from individual to individual showing the need for comprehensive analyses.